Unveiling the infrared complex dielectric function of ilmenite CdTiO3 - Rodrigues, João E.F.S.; Ferrer, Mateus M.; Moreira, Mario L.; Sambrano, Julio R. [UNESP]; Costa, Renilton C.; Rodrigues, Ariano D.; Pizani, Paulo S.; Huttel, Y.; Alonso, José A.; Pecharromán, Carlos (Elsevier, 2020)
This work presents the infrared active modes of the ilmenite phase of CdTiO3. Since the ilmenite phase of cadmium titanate is unstable in large particle size, the dielectric tensor at the infrared region has been extracted from near normal reflectance of highly reflecting cold pressed powder pellets. The microscopic values of each tensor component were deduced by a new formulation of the effective medium model suitable for anisotropic compacts. This model explicitly takes into account both the matrix and void percolation thresholds, in order to properly determine the dielectric tensor at the region of high frequency longitudinal modes. Both, reflection and absorption experimental data are been confronted with theoretical calculations based on the density functional theory, revealing a great convergence of the values. Additionally, we estimated the quality factor in the microwave region to be: εsx ∼27, εsz ∼20, and Qu × f ∼111,000 GHz (at 10 GHz), enabling the ilmenite CdTiO3 material to be employed as central element in circuitry operating at IEEE X-band.
Keywords: CdTiO3; Effective medium theory; Ilmenite; Infrared reflectivity; Lattice dynamics; Microwave dielectrics